THE ROLE OF LAWIN SOCIALJUSTICE:BRIDGING THE GAPBETWEEN LEGISLATION AND REALITY IN PAKISTAN - Muhammad Abbas Sabri; Muhammad Shahid Sultan; Dr. Noreen Akhtar; Zulfiqar Husaain (Policy Research Journal, 2025)
This paper examines the role of law in the context of Pakistan; therefore, it supports the argument of how law strengthens social justice to reform injustice into justice and protect the rights of oppressed groups besides ordering society. However, major discrepancies remain between the idea of legal reform in Pakistan as provisioned by its official legislation and the actual realities of the situation. The present paper aims to describe the historical development of laws in Pakistan regarding social justice and assess the systematic problems related only to the Pakistani context, namely corruption, lack of political willingness, and patriarchy, and to overcome them. Most attention is accorded to the failure between passing legal frameworks and implementation that sustains unfairness. Based on the lessons from Pakistan's legal, cultural and political environments, this study reveals the need for strong enforcement measures, awareness and technological interventions to fill the gap. According to these systemic factors, the paper outlines pragmatic recommendations for changing the structure towards an equal society.